Emotional vocabulary in religious discourse (on the basis of German treatises Meister Eckhart) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article deals with the possibility of expressing basic emotions at the lexical level in a specific type of texts of religious discourse – treatise. The dynamic of emotional vocabulary in German treatises Meister Eckhart in terms of experiencing emotions is analyzed.
Keywords: emotional vocabulary; religious discourse; treatise; positive emotional vocabulary; negative emotional vocabulary; ambivalent emotional vocabulary